2008
DOI: 10.1098/rspb.2007.1199
|View full text |Cite
|
Sign up to set email alerts
|

How populations persist when asexuality requires sex: the spatial dynamics of coping with sperm parasites

Abstract: The twofold cost of sex implies that sexual and asexual reproduction do not coexist easily. Asexual forms tend to outcompete sexuals but may eventually suffer higher extinction rates, creating tension between short-and long-term advantages of different reproductive modes. The 'short-sightedness' of asexual reproduction takes a particularly intriguing form in gynogenetic species complexes, in which an asexual species requires sperm from a related sexual host species to trigger embryogenesis. Asexuals are then p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 66 publications
(113 reference statements)
2
71
1
Order By: Relevance
“…Furthermore, they most likely also receive less sperm than P. latipinna. Regardless of how much sperm is really needed to fertilize a whole clutch, this strongly suggests that wild P. formosa are sperm limited and underscores the role of male mate choice as a stabilizing factor in this system (see also Kokko et al 2008). However, more research is needed to investigate how male mate choice influences life-history characteristics in this and other sexual/asexual mating complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they most likely also receive less sperm than P. latipinna. Regardless of how much sperm is really needed to fertilize a whole clutch, this strongly suggests that wild P. formosa are sperm limited and underscores the role of male mate choice as a stabilizing factor in this system (see also Kokko et al 2008). However, more research is needed to investigate how male mate choice influences life-history characteristics in this and other sexual/asexual mating complexes.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the amount of sperm found in the genital tracts of sexual and asexual females as a proxy for male mate choice. Based on a recent metapopulation model, male mate choice and sperm limitation of asexuals are two factors predicted to drive such species complexes towards stability (Kokko et al 2008). Hence, this is the first study that links behavioural patterns observed in the laboratory with fitness-relevant sperm transfer in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…These works either assumed the twodeme model (Hellriegel and Reyer 2000), or searched for dispersal-extinction equilibria in a metapopulation framework (e.g. Kokko et al (2008)). Interestingly, Kokko et al (2008) showed that metapopulation dynamics alone may promote stable coexistence.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the competitive exclusion of the sexual species will not be detrimental to the parthenogenetic species. Competitively excluding a host is, on the contrary, extremely detrimental for sperm parasites such as gynogenetic species, unless the two species follow metapopulation dynamics (Kokko et al 2008). The focus of this study was to test the predictions of the Schley et al (2004) model by examining if a gynogenetic species is a less efficient competitor than its sexual host.…”
mentioning
confidence: 99%
“…Vrijenhoek (1984), Schley et al (2004), and Kokko et al (2008) all proposed ecological mechanisms that could aid the coexistence between a sperm-dependent unisexual lineage and its host such as niche differentiation (frozen niche variation hypothesis), differential competitive abilities, or spatial structure. Additionally, Moore and McKay (1971), Kaweki (1989), Lima et al (1996), and Heubel et al (2009) all proposed models based on how sexual selection and the inability to properly discriminate against heterospecific females by males of the host species may affect coexistence in the long term.…”
mentioning
confidence: 99%